(untitled) (Theatrum historiae, 2017)
The main aim of the contribution is to show upon the background of the diplomatic missions of the Habsburg diplomats – Allegretto Allegretti and Johann Theodor of Lorbach (1655–1656), Johann Christoph of Fragstein and Christoph Beuer of Binnen (1657–1658) – how the ceremonial and ritual practices at the Tsar’s court were perceived by these mentioned diplomats. Furthermore, how there were reflected particular means of visualisation of the political status of the Habsburg representatives on the one hand and of the Russian head of state and his councellors and advisers on the other hand. These mutual encounters of at the first sight completely different worlds of thoughts and value systems could not avoid cultural clashes and misunderstandings (the arguments about the usage of right titles, about rules of precendence, the Tsar’s inappropriate gestures during official meetings, the Russians, imposing of their arrogant behaviour on the Habsburg diplomats).